PENINGKATAN KUALITAS PEMBELAJARAN IPA MELALUI MODEL SETS BERBANTUAN MEDIA POWER POINT - Nur Khomsah; Sri Hartati; Florentina Widi Hastrini (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2017)
The purpose of research is to improve the quality of scienceinstructionalthrough Science Enviroment Technology and Society (SETS) model assisted by Power Point media in primary IVA SD Islam Hidayatullah. This research used classroom action research, it conducted in three cyles, each consisting in one meeting with stages of planning, observation, action, and reflection. Data collection techniques were using tests and nontest. The Data were analyzed using quantitative and qualitativeanalysis.The results showed the teacher skills in the first cycle scored 25(enough), the second cyclewas35with (good), the third cycle was40(very good). Students activity score in the first cycle was 23,7 (enough), the second cycle was 27,5 (good), the third cycle was36,5(very good). The student response in the first cycle scored101 (unfavorable)the second cyclewas119with (good), the third cycle was138 (very good).Classical completeness in the first cycle was50percent (incomplete), the second cycle was70,6percent (incomplete), the third cycle was88,2percent(complete).The Conclusion of this researchis the SETS model assisted by Power Point media can improve science instructional in primary IVA SD Islam Hidayatullah Semarang.